Peran pemerintah dan industri jasa keuangan dalam mendukung transformasi digital UKM - Adrian Adrian; Samuel Horas Sarjana (LPMP Imperium, 2023)
This article provides information about the role of the Government and Financial Services Industry in Supporting the Digital transformation of Micro, Small, and Medium Enterprises (MSMEs) to improve Indonesia’s economy. Methodology through Literature Research. Micro, Small, and Medium Enterprises (MSMEs) as productive economic enterprises owned by individuals and business entities, based on a survey by the Ministry of Cooperative SMEs in March 2021, amounted to 64.2 million by contributing to Gross Domestic Product (GDP) 61.07% or Rp. 8,573.89 trillion. Digital-based MSME growth is targeted at 24 million in 2023 and 30 million in 2024, while digital-based modern cooperatives are targeted for 400 units in 2023 and 500 units in 2024. Digital transformation of MSMEs not only encourages the use of the marketplace but can also collaborate and increase production capacity so that they can go public and go international—growth in the number of MSMEs in terms of their number and contribution to the economy. Public interest statement This article aims to see how effective education and financial literacy for MSMEs by the government and financial institutions can encourage MSMEs to go digital in managing their business. Article history Received 21 Dec 2022 | Revised 27 Dec 2022 | Accepted 31 Dec 2022 | Online First 03 Feb 2023